Implementation of the Independent Curriculum Policy: Challenges and Opportunities for Teachers and Students - Novayanti Sopia Rukmana (Universitas Sulawesi Barat, 2023)
This research evaluates the challenges and opportunities in the implementation of the Merdeka Belajar Kampus Merdeka (MBKM) Curriculum in Indonesia, focusing on teacher readiness, infrastructure, assessment methods, and 21st century skills development. Data shows that although most teachers in urban areas have received adequate training, gaps still occur in remote areas. Disparities in infrastructure and technology access between urban and rural areas are also a significant obstacle. However, the implementation of MBKM has shown positive results in improving students' critical thinking, creativity, collaboration and communication skills. This study proposes increased continuous training for teachers, technological infrastructure development, as well as innovations in assessment methods as solutions. With continued support from the government, educational institutions, and the private sector, MBKM has great potential to improve the quality of education and prepare Indonesia's young generation for global challenges.